Privacy and the role of international law in the digital age - Yilma, Kinfe (Oxford data protection & privacy law, 2023)
"This book examines the role of international law in securing privacy and data protection in the digital age. Driven mainly by the transnational nature of privacy threats involving private actors as well as States, calls are increasingly made for an âinternationalâ privacy framework to meet these challenges. Mapped against a flurry of global privacy initiatives, the book provides the first comprehensive analysis of the extent to which and whether international law attends to the complexities of upholding digital privacy. The book starts by exploring boundaries of international privacy law in upholding privacy and data protection in the digital ecosystem where threats to privacy are increasingly transnational, sophisticated and privatized. It then explores the potential of global privacy initiatives, namely Internet bills of rights, universalization of regional systems of data privacy protection, and the multi-level privacy discourse at the United Nations, in reimagining the normative contours of international privacy law. Having shown limitations of global privacy initiatives, the book proposes a pragmatic approach that could make international privacy law better-equipped in the digital age"-- Provided by publisher